Tgf-β1 expression as a biomarker of poor prognosis in prostate cancer - Sabrina Thalita dos Reis; Jose Pontes-Júnior; Alberto Azoubel Antunes; Juliana Moreira de Sousa-Canavez; Daniel Kanda Abe; José Arnaldo Shiomi da Cruz; Marcos Francisco Dall'Oglio; Alexandre Crippa; Carlo Camargo Passerotti; Leopoldo A Ribeiro-Filho; Nayara Izabel Viana; Miguel Srougi; et al. (Clinics, 2011)
OBJECTIVE: To evaluate the correlation between transforming growth factor beta (TGF-β1) expression and prognosis in prostate cancer. PATIENTS AND METHODS: TGF-β1 expression levels were analyzed using the quantitative real-time polymerase chain reaction to amplify RNA that had been isolated from fresh-frozen malignant and benign tissue specimens collected from 89 patients who had clinically localized prostate cancer and had been treated with radical prostatectomy. The control group consisted of li patients with benign prostate hyperplasia. The expression levels of TGF-β1 were compared between the groups in terms of Gleason scores, pathological staging, and prostate-specific antigen serum levels. RESULTS: In the majority of the tumor samples, TGF-β1 was underexpressed 67.0% of PCa patients. The same expression pattern was identified in benign tissues of patients with prostate cancer. Although most cases exhibited underexpression of TGF-β1, a higher expression level was found in patients with Gleason scores >7 when compared to patients with Gleason scores <7(p = 0.002). Among the 26 cases of TGF-β1 overexpression, 92.3% had poor prognostic features. CONCLUSIONS: TGF-β1 was underexpressed in prostate cancers; however, higher expression was observed in tumors with higher Gleason scores, which suggests that TGF-β1 expression may be a useful prognostic marker for prostate cancer. Further studies of clinical specimens are needed to clarify the role of TGF-β1 in prostate carcinogenesis.